(untitled) (Journal of Plant Disease Sciences, 2017)
Field experiment was conducted for the management of stemphylium blight incited by of garlic during 2012-14. Stemphylium vesicarium Rabi Among seven fungicides evaluated under field conditions on the basis of pooled data Foliar sprays of Tebuconazole @ 0.1% was found significantly superior to minimize the leaf blight of garlic (PDI 1.90%) which was at par with Azoxystrobin @ 0.1% PDI 2.74%. The maximum percent disease control (PDC) was recorded with four sprays at ten days interval initiated at the onset of disease. Tebuconazole @ 0.1% (89.29%) followed by Azoxystrobin @ 0.1% (84.55%). Four foliar sprays of Tebuconazole @ 0.1% recorded significantly superior yield (168.82 q/ha) which was at par with Azoxystrobin @ 0.1% (164.60 q/ha).